Treating codeine dependence with buprenorphine: Dose requirements and induction outcomes from a retrospective case series in New South Wales, Australia. (30th July 2015) - Nielsen, Suzanne; Bruno, Raimondo; Murnion, Bridin; Dunlop, Adrian; Degenhardt, Louisa; Demirkol, Apo; Muhleisen, Peter; Lintzeris, Nicholas
Abstract: Introduction and Aims: Codeine dependence is an emerging public health concern, yet no studies have specifically examined the treatment of codeine dependence. Given the lower potency of codeine it cannot be assumed that buprenorphine dose requirements for heroin dependence will generalise to codeine. This is the first study to examine buprenorphine treatment for codeine dependence. Design and Methods: Retrospective case series of 19 codeine‐dependent treatment entrants who received sublingual buprenorphine maintenance treatment through six specialist inpatient and outpatient treatment centres. Baseline codeine doses and buprenorphine dose at days 7 and 28 were collected, in addition to details on general demographics, pain and mental health, substance use and outcomes after 28 days of buprenorphine treatment. Results: A significant linear relationship was found between initial codeine dose and dose of buprenorphine given at days 7 and 28 for the codeine dose range of 50–960 mg day −1 (mean: 564 mg; 95% confidence interval 431–696 mg). Median buprenorphine dose was 12.0 mg (interquartile range 9.5 mg, range 4–32 mg) at day 7 and 16.0 mg (interquartile range 13.5 mg, range 4–32 mg) at day 28. Buprenorphine doses received were markedly higher than estimated codeine doses based on standard dose conversion tables. Discussion and Conclusions: With increasing presentations relating to codeine dependence, these findings provide important guidance to clinicians. Buprenorphine doses were consistently higher than doses estimated based on the dose of codeine consumed, and were comparable with doses used in the treatment of dependence with heroin and more potent prescription opioids. [Nielsen S, Bruno R, Murnion B, Dunlop A, Degenhardt L, Demirkol A, Muhleisen P, Lintzeris N. Treating codeine dependence with buprenorphine: Dose requirements and induction outcomes from a retrospective case series in New South Wales, Australia. Drug Alcohol Rev 2015]